Automation to pneumatic conveyors aiming to laboratory studies - Storino, Yuri Silva Cruz; Lima, Carlos José de (Brazilian Journal of Production Engineering, 2024)
Laboratory studies are necessary in several areas and aim to increase efficiency in manufacturing, production, transport and other functions, with part of these studies being carried out in universities, thus making it viable to use new technologies to assist in the execution of these developments. This article aims to present automation for pneumatic conveyors focus at laboratory studies, using low-cost technologies. The Arduino platform was used to control the automation, MPS20N0040D-S pressure sensors and DHT11 humidity sensors for data acquisition, and a power circuit to control the grain feeder, in addition to displaying the acquired data and providing digital reports thereof. The experiments showed that it was possible to have centralized digital control and monitoring, with just one operator, with the ability to generate reports with measurements every second. Thus, it was possible to verify that the use of this automation reduces the time for data acquisition, the operators needed to conduct experiments and operator errors. These added to the low-cost components demonstrate the viability of automation.
Keywords: Arduino; Automation; Laboratory Studies; Pneumatic Conveyors